Message - Yusuf, Felix Sunday (Universal Journal of Pharmaceutical Research, 2018)
Universal Journal of Pharmaceutical Research, as a specialty journal is a double blind peer-reviewed informational journal that provides rapid publication (bi-monthly) of original research papers, scientific commentaries, views and review articles, and editorial commentary in the gamut of pharmaceutical sciences. It is no secret that the landscape of scholarly publishing is quickly changing, getting more innovative. Across disciplines, new demands and expectations from both authors and readers (visitors) have encouraged shifting perspectives and strategies among editors and publishers. Our primary goal as a team is to ensure that The Universal Journal of Pharmaceutical Research remains flexible and innovative in attending to the rapidly shifting scientific communication landscape, while also maintaining and intensifying the high standards and best practices for which the journal is known. Our journey so far has been encouraging, aligning with our mission and tending towards our vision, comprising of review articles and outstanding and translational research in the field of pharmaceutical science and technology. UJPR editorial board ensure top notch manuscripts are accepted for publication through rigorous double blind peer review process, manned by the editors and a panel of strictly chosen experts in the field. Furthermore, the open access provides has been a rewarding strategy as UJPR finds it a considerable advantages over conventional journals of pharmaceutical sciences with greater visibility and impact. The journal welcomes publications of high quality papers on theoretical and practical applications in pharmaceutical science and technology. Original research papers, state-of-the-art reviews, and high quality technical notes are invited for publication. By steadily introducing initiatives to the editorial and review processes, I believe The Universal Journal of Pharmaceutical Research (UJPR) will further develop as a flagship for communicating pharmaceutical research and related field, all while successfully meeting the evolving needs of its audience. I congratulate all editorial board members and authors for their efforts and believe for great success of Universal Journal of Pharmaceutical Research.''